2016
DOI: 10.1016/j.addbeh.2016.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Caffeinated and non-caffeinated alcohol use and indirect aggression: The impact of self-regulation

Abstract: Research shows that heavier alcohol use is associated with physical aggression. Scant research has examined the way in which alcohol relates to other forms of aggression, such as indirect aggression (e.g., malicious humor, social exclusion). Given the possible negative consequences of indirect aggression and the limited evidence suggesting alcohol use can elicit indirectly aggressive responses, research is needed to further investigate the association between drinking behavior and indirect aggression. Addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 64 publications
(107 reference statements)
0
7
0
Order By: Relevance
“…Knowledge regarding the specific forms of aggression associated with alcohol has been limited by the way aggression has been operationalized in past event-level research (Tomlinson et al, 2016), typically analyzed as an overarching aggression score encompassing multiple forms of aggression (Neal & Fromme, 2007). In fact, the dearth of information on the types of aggression associated with alcohol has been argued to be a limitation across the field of alcohol-related aggression (Sheehan, Linden-Carmichael, & Lau-Barraco, 2016). Thus, questions remain about the specific types of aggression that are more likely to be associated with drinking.…”
Section: Focus On Overt Forms Of Aggressionmentioning
confidence: 99%
“…Knowledge regarding the specific forms of aggression associated with alcohol has been limited by the way aggression has been operationalized in past event-level research (Tomlinson et al, 2016), typically analyzed as an overarching aggression score encompassing multiple forms of aggression (Neal & Fromme, 2007). In fact, the dearth of information on the types of aggression associated with alcohol has been argued to be a limitation across the field of alcohol-related aggression (Sheehan, Linden-Carmichael, & Lau-Barraco, 2016). Thus, questions remain about the specific types of aggression that are more likely to be associated with drinking.…”
Section: Focus On Overt Forms Of Aggressionmentioning
confidence: 99%
“…For example, alcohol intoxication has been linked to increased risk for engaging in violent behavior (e.g., Giancola et al, 2011), as well as for demonstrating indirect aggression such as social manipulation or bullying (Crane, Licata, Schlauch, Testa, & Easton, 2017). In a study of bystander intervention, Sheehan, Linden-Carmichael, and Lau-Barraco (2016) were able to demonstrate both that alcohol intoxication was linked to an increased risk for participating in sexual violence, and that men who met the criteria for heavy drinking were also less likely to intervene when witnessing a sexually violent act in comparison to their peers who consumed less alcohol.…”
Section: Introductionmentioning
confidence: 99%
“…As for the quality assessment, a total of 25 articles showed a poor quality rating, which means with important limitations that could invalidate the results and high risk of bias in general [ 23 , 24 , 25 , 26 , 27 , 31 , 34 , 36 , 38 , 40 , 41 , 43 , 44 , 45 , 46 , 47 , 48 , 55 , 56 , 57 , 58 , 60 , 61 , 62 , 63 , 64 ]. A total of 15 assessed studies reported a fair quality rating, with no known important limitation that could invalidate the results and with a moderate or acceptable risk of bias [ 28 , 29 , 30 , 35 , 37 , 42 , 49 , 50 , 51 , 52 , 53 , 54 , 58 , 61 ] and only two studies reported a good quality rating with all criteria met and a very low risk of bias [ 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…For meta-regression analysis, sample size, gender and age of participants, WHO Regions location (European Region, African Region, Region of the Americas, South-East Asia Region, Eastern Mediterranean Region, Western Pacific Region), years since publication and methodological quality of the studies were considered as possible sources of heterogeneity; the time considered to assess AmED consumption was also included into the meta-regression analysis by considering four subgroups (Past week, Past 30-days, Past 60-days, Past 90-days and Past year). Three articles [ 23 , 24 , 25 ] were excluded from the meta-analysis and meta-regression analyzes because they did not report the prevalence rate of AmED consumption. Two other papers were excluded because they involved the same cohort of participants [ 26 ].…”
Section: Methodsmentioning
confidence: 99%